Fenbendazole and its synthetic analog interfere with HeLa cells' proliferation and energy metabolism via inducing oxidative stress and modulating MEK3/6-p38-MAPK pathway. (1st July 2022) - Peng, Yi; Pan, Jie; Ou, Fengting; Wang, Wenchao; Hu, Haihong; Chen, Lu; Zeng, Su; Zeng, Kui; Yu, Lushan
Abstract: Fenbendazole, a broad-spectrum anti-parasitic drug, can be a potential anti-tumor agent. In this study, we synthesized and purified its derivative, analog 6, intending to achieve improved efficacy in cancer cells and decreased toxicity in normal cells. To evaluate in vitro anti-tumor activities of fenbendazole and analog 6 in different cancer cell lines, a CCK-8 assay was performed, and we found that human cervical cancer HeLa cells were more sensitive to analog 6 than to fenbendazole. Furthermore, we explored the associated mechanism, and our results showed that analog 6 and fenbendazole could induce oxidative stress by accumulating ROS. It not only activated the p38-MAPK signaling pathway, thereby inhibiting the proliferation of HeLa cells and enhancing the apoptosis of HeLa cells, but also significantly induced impaired energy metabolism and restrained their migration and invasion. In addition, the modified analog 6 showed reduced toxicity to normal cells without decreased anti-cancer effect. In conclusion, fenbendazole and analog 6 have multiple targets and strong anti-tumor effects on HeLa cells in vitro and in vivo . The optimized analog 6 could inhibit the viability of HeLa cells with lower toxicity than normal human cells, promising to be developed as an antitumor active compound. Graphical abstract: Image 1 Highlights: Anti-tumor effects of Fenbendazole and analog 6 (6/F) in HeLa cells were evaluated. Results showed that 6/F inhibited the proliferation of HeLa cells. 6/F impaired energy metabolism and induced oxidative stress in HeLa cells. Modified analog 6 showed reduced toxicity in vitro and in vivo. 6/F are potential candidates for anti-tumor therapy.